Increasing Body Mass Index Predicts Rapid Decline in Renal Function: A 5 Year Retrospective Study - Ma, Xiaojing; Zhang, Chengyin; Su, Hong; Gong, Xiaojie; Kong, Xianglei (Hormone and Metabolic Research, 2018)
While obesity is a recognized risk factor for chronic kidney disease, it remains unclear whether change in body mass index (ΔBMI ) is independently associated with decline in renal function (evaluated by the change in estimated glomerular filtration rate, ΔeGFR) over time. Accordingly, to help clarify this we conducted a retrospective study to measure the association of ΔBMI with decline in renal function in Chinese adult population. A total of 4007 adults (aged 45.3±13.7 years, 68.6% male) without chronic kidney disease at baseline were enrolled between 2008 and 2013. Logistic regression models were applied to explore the relationships between baseline BMI and ΔBMI, and rapid decline in renal function (defined as the lowest quartile of ΔeGFR ). During 5 years of follow-up, the ΔBMI and ΔeGFR were 0.47±1.6 (kg/m2) and –3.0±8.8 (ml/min/1.73 m2), respectively. After adjusted for potential confounders, ΔBMI (per 1 kg/m2 increase) was independently associated with the rapid decline in renal function [with a fully adjusted OR of 1.12 (95% CI, 1.05 to 1.20). By contrast, the baseline BMI was not associated with rapid decline in renal function [OR=1.05 (95% CI, 0.98 to 1.13)]. The results were robust among 2948 hypertension-free and diabetes-free participants, the adjusted ORs of ΔBMI and baseline BMI were 1.14 (95% CI, 1.05 to 1.23) and 1.0 (95% CI, 0.96 to 1.04) for rapid decline in renal function, respectively. The study revealed that increasing ΔBMI predicts rapid decline in renal function.
Keywords: body mass index; renal function; proteinuria; estimated glomerular filtration rate; epidemiology